Debt policy and firm performance of family firms: the impact of economic adversity. Issue 3 (5th June 2017) - Vieira, Elisabete Simões
Abstract : Purpose: The purpose of this paper is to analyse the relationship between debt policy and performance among family firms (FF), providing evidence on whether FF differ from non-family firms (NFF). It also focusses on the possibility of asymmetrical debt policy impact on performance between periods of stability and economic adversity. Design/methodology/approach: The paper employs panel data regression, considering a sample of Portuguese listed firms for the period between 1999 and 2014. Findings: Overall, the author find evidence that debt contributes negatively to firms' performance, which is consistent with the pecking order prediction, and that the relationship between debt and performance do not differ significantly between FF and NFF. After addressing the endogeneity issue, the author conclude that firms' performance is negatively influenced by both short- and long-term debt. Considering the total debt, the negative relationship between the two variables differs from family and non-family companies. The results show that age and size influences positively, and the independence of the board directors influences negatively the firms' performance. The empirical findings suggest that under economic adversity, the firms' performance is negatively affected. Finally, the author conclude that return on assets appear to fit better than return on equity or MB when you want to relate debt and firm performance. Research limitations/implications: A limitation of this study is the small size of the Euronext Lisbon that results in a small sample. Originality/value: This paper offers some insights on the relationship between debt policy and firm performance from a country with weak protection of minority shareholders, concentrated ownership and a significant family control. It also gives the opportunity to analyse whether firm performance differs according to market conditions.